Evaluation of certain tuberose (Polianthes tuberose L.) double genotypes for assessing the yield and quality traits under agro climatic conditions of Telangana - K.SUSHMA, K. DHANUMJAYA RAO and (The Journal of Research, PJTSAU, 2017)
An experiment on the Evaluation of certain Tuberose double genotypes was conducted for four consecutive years from 2010 to 2014 at Floricultural Research Station, Hyderabad for the identification of a suitable variety for the cultivation in Telangana State. Maximum average plant height (43.2 cm), spike length (88.2 cm), no. of spikes / plant (2.7), rachis length (41.3cm), vase life (7.3 days), no. of bulbs/plant (72.8) and minimum days to flowering (66.5) were recorded in Calcutta double over check Hyderabad double. No. of leaves per plant (29.9) and floret length (5.8 cm) were recorded maximum in Vaibhav over check. No. of florets/spike (40.0) and floret diameter (4.3 cm) were recorded maximum in Suvasini over control. Size of bulb was recorded maximum in Hyderabad double (1.7).